STUDENTS’ ABILITY IN COMPREHENDING ENGLISH READING TEXTS AT SMAN 1 XIII KOTO KAMPAR - Fatimah, Siti; Novitri, Novitri; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was aimed to find out how is the students’ ability in comprehending English reading texts at SMAN 1 XIII Koto Kampar. The design of the research was one class for the try-out test and one class for the real test. The population was the eleventh-grade students of academic 2020/2021. The sample was 25 students of class XI MIPA 2 which were chosen by using a lottery. The data were collected by giving a test with 50 multiple-choice questions. Question number 1-25 deals with descriptive text, and 26-50 was recount text. The result of the data shows that the mean score of the students' ability in comprehending English reading texts is 55.52 which means categorized into the mediocre level. The mean score of the students' ability in comprehending descriptive text is 56.8 and categorized into the mediocre level, the difficult aspect for students in comprehending descriptive text is in identifying reference with the mean score is 53.32 that categorized into mediocre level and the easiest aspect is in finding main idea with the mean score is 65.32 and categorized into good level. In recount text, the researcher found out that the mean score is 54.24 which categorized into mediocre level, the difficult aspect for students in comprehending recount text is in finding social function with the mean score is 44 and categorized into mediocre level. Otherwise, the easiest aspect is in identifying inference with the mean score is 61.32 and categorized into good level.Key Words: Students’ Ability, Reading Comprehension, Descriptive Text, Recount Text